5
$\begingroup$

let $a,b,n$ be positive integer numbers,and such $a,b\le n$, show that $$\dfrac{1}{n}\sum_{k=0}^{n-1}\binom{k}{a}\binom{k}{b}\le\dfrac{1}{a+b+1}\binom{n}{a}\binom{n}{b}$$

this inequality maybe can use Integral inequality to solve it.because $$\int_{0}^{1}x^{a+b}dx=\dfrac{1}{a+b+1},\int_{0}^{1}x^{n-1}dx=\dfrac{1}{n}$$

Thank you for you help.

$\endgroup$
5
+50
$\begingroup$

Since the inequality is symmetric in $a$ and $b$ we may (and will), suppose $a\leq b\leq n$.

Moreover, the inequality is trivially satisfied if $n=b$. So let us suppose that the inequality is proved for some $n\geq b$. It follows that $$\eqalign{ \sum_{k=0}^n\binom{k}{a}\binom{k}{b}&=\sum_{k=0}^{n-1}\binom{k}{a}\binom{k}{b}+ \binom{n}{a}\binom{n}{b} \cr &\leq \frac{n}{a+b+1}\binom{n}{a}\binom{n}{b}+\binom{n}{a}\binom{n}{b}\cr &\leq \frac{a+b+n+1}{a+b+1}\binom{n}{a}\binom{n}{b}\cr} $$ Now the desired inequality for $n+1$ would follow if we have $$ \frac{a+b+n+1}{a+b+1}\binom{n}{a}\binom{n}{b}\leq \frac{n+1}{a+b+1}\binom{n+1}{a}\binom{n+1}{b} $$ This is equivalent to $$ (n+1+a+b)(n+1-a)(n+1-b)\leq(n+1)^3 $$ or $$ n+1 \geq \frac{a^2b+b^2a}{a^2+b^2+ab}=b-\frac{b^3}{a^2+ab+b^2} $$ and this inequality is trivially satisfied since $n+1>b$. This ends the proof by induction.$\qquad\square$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.